Effects of medicine food Fructus Gardeniae on liver and kidney functions after oral administration to rats for 12 weeks. Issue 7 (4th June 2021) - Li, Chunnan; Gao, Xu; Gao, Xiaochen; Lv, Jingwei; Bian, Xuefeng; Lv, Jinpeng; Sun, Jiaming; Luo, Guangming; Zhang, Hui
Abstract: Fructus Gardeniae (FG) is medicine food widely used for the treatment and prevention of various diseases. However, in recent years, research has suggested that high doses of FG can cause hepatotoxicity and nephrotoxicity. To assess this potential toxicity in more depth, this study investigated the effects of decocted FG and two of its bioactive constituents (geniposide and genipin) on liver and kidney function in rats. Rats were intragastrically administered FG (330 mg/kg body weight), geniposide (50 mg/kg body weight), or genipin (50 mg/kg body weight) for 12 weeks. Changes in body weight, liver and kidney indices, biochemical indices, and inflammatory factors were monitored. In addition, pathological sections were assessed and the expression of caspase‐3, NF‐κBp65, COX‐2, and iNOS was detected by immunohistochemistry and Western blot. It was found that the levels of aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, creatinine, and urea nitrogen increased following administration of FG, geniposide, and genipin. Furthermore, the activities of superoxide dismutase and reduced glutathione decreased following treatment, while malondialdehyde levels increased. Pathological and immunohistochemical evaluations further confirmed that FG and its constituents may cause damage to the liver and kidneys. The mechanism study revealed that the protein level of inflammatory pathway increased and further promoted apoptosis, suggesting that it should not be taken orally for extended periods of time. Practical applications: Chinese medicine and food safety have always been public health concerns. Fructus Gardeniae (FG) is a plant with a dual‐purpose as it is used as both a medicine and food. Medicinally, it has the effects of heat‐clearing and detoxification. However, its adverse effects and related mechanisms are not clear, and this has potential safety implications. In this study, rats were treated with FG for 12 weeks and found that the long‐term administration of FG or high dosing can lead to damage to liver and kidney function. Therefore, close attention must be paid to the dosage of FG in order to achieve a therapeutic effect and avoid adverse reactions. Thus, this study lays a foundation for the safety evaluation and clinical application of FG. Abstract : Through this study, it was found that Fructus Gardeniae which was taken orally by rats for 12 weeks, had liver and kidney toxicity. Therefore, close attention must be paid to the dosage of Fructus Gardeniae in order to achieve a therapeutic effect and avoid adverse reactions.